Artificial Intelligence in Vocational Education and Training: A Critical Analysis - R. Ravichandran,; Mahapatra, Jayashree (SCHOOL SCIENCE, 2025)
Artificial Intelligence (AI) has revolutionised the way we live and work, and its impact is felt across many sectors. In recent years, the application of AI in Vocational Education and Training (VET) has garnered significant attention. This paper aims to critically analyse the role of AI in VET, highlighting its potential benefits and drawbacks. It explores how AI can enhance the learning experience of students by providing personalised and adaptive training. However, the paper also argues that the integration of AI in VET must be done with caution, as it could result in job losses and exacerbate existing inequalities in the labour market. Ultimately, the paper concludes that AI in VET should be used as a complementary tool to support human learning, rather than replace it.